Iron Overload in Patients Undergoing Hematopoietic Stem Cell Transplantation - Vinod Pullarkat (Advances in Hematology)
Recipients of hematopoietic stem cell transplantation (HSCT) frequently have iron overload resulting from chronic transfusion therapy for anemia. In some cases, for example, in patients with myelodysplastic syndromes and thalassemia, this can be further exacerbated by increased absorption of iron from the gut as a result of ineffective erythropoiesis. Accumulating evidence has established the negative impact of elevated pretransplantation serum ferritin, a surrogate marker of iron overload, on overall survival and nonrelapse mortality after HSCT. Complications of HSCT associated with iron overload include increased bacterial and fungal infections as well as sinusoidal obstruction syndrome and possibly other regimen-related toxicities. Based on current evidence, particular attention should be paid to prevention and management of iron overload in allogeneic HSCT candidates, especially in patients with thalassemia and myelodysplastic syndromes. The pathophysiology of iron overload in the HSCT patient and optimum strategies to deal with iron overload during and after HSCT require further study.